Gestión de talento humano y su efecto en la Atención a los usuarios del GAD municipal del Cantón pichincha. Propuesta para mejorar el servicio al usuario - Vélez García, Carmen Aracely (2021)
Actually, the management of people, as well as the attention they provide to external users or clients is a key issue for any organization or institution whatever its size or economic activity developed. This work, is an investigation that deals with the management of Human Talent and its impact on the attention of users of the Municipal Decentralized Autonomous Government of the Canton Pichincha, field research has been carried out in the canton Pichincha, observing existing lacks in the way of the attention provided to the citizens once they went to carry out their formalities in this municipal institution. The information was collected through the survey technique aimed at users leaving the Municipal GAD of the Canton Pichincha, which serve as guidance to make the proposal to develop a guide to optimize the services and the good performance of employee functions and adequate attention to users. The purpose of this project is to contribute to a staff-oriented optimization proposal, including tactics, actions, systems for leveraging their capabilities, their skills and available inputs to develop efficient work. Following the completion of the report, which includes analysis and interpretation of the results of the research carried out, a number of conclusions and recommendations have been reached to promote the improvement of the institution in which this research was conducted. Keywords: Public Administration, Human Talent Management, Training, Work Performance, Attention to Users, Institutional Image.